Spatial distribution and stocks of bivalve mollusk Mercenaria stimpsoni in the costal waters of Primorye - Roman V. Vlasenko (Известия ТИНРО, 2015)
Results of SCUBA-diving survey are presented that is conducted in the coastal waters of Primorye at the depth < 20 m in summer and fall of 2002-2014 (in total about 12,000 diving stations in the area 2300 km2). Spatial distribution of Mercenaria stimpsoni is mapped using the geo-informational system MapInfo Professional, its total abundance and biomass is assessed by the method of Voronoy diagrams (same as Tissen polygons). The mollusk distributes widely but in dependence on environmental conditions, with preference to surfy-alluvial and surfy-erosion bays with sandy and muddy-sandy grounds, particularly to long surfy coastline. In Peter the Great Bay it forms settlements at the depth 1.5-15.0 m (maximum abundance at 4-10 m), in the area from Cape Povorotny to Cape Ostrovnoy - at the depth 2-16 m (maximum abundance at 10-16 m), and in the area from Cape Ostrovnoy to Cape Zolotoy - at the depth 2-20 m (maximum abundance at 14-20 m). Obviously, the habitat of M. stimpsoni shifts to the greater depth with wave action increasing. The total stock of M. stimpsoni in the coastal waters of Primorye is estimated as 25,000 t for the area over 100 km2. The stock is distributed mainly eastward from Cape Povorotny where 85 % of its settlements (by area) and 91.5 % of total stock are located.